Genetics of sex determination - Verma, Ram S. (Ram Sagar) (Advances in genome biology, 1996)
The Genetical Theory of Natural Selection by R.A. Fisher (1930) dictated that sexual dimorphisms may depend upon a single medelian factor. This could be true for some species but his suggestion could not take off the ground as gender in Drosophila is determined by the number of X chromosomes. Technical advances in molecular biology have revived the initial thinking of Fisher and dictate that TDF or SRY genes in humans or Tdy in mice are sex determining genes. The fortuitous findings of XX males and XY female, which are generally termed sex reversal phenomenon, are quite bewildering traits that have caused much amazement concerning the pairing mechanism(s) of the pseudoautosomal regions of human X and Y chromosomes at meiosis. These findings have opened new avenues to explore further the genetic basis of sex determination at the single gene level. The aim of the fourth volume, titled Genetics of Sex Determination is to reflect on the latest advances and future investigative directions, encompassing 10 chapters. Commissioned several distinguished scientists, all pre-eminent authorities in each field to shed their thoughts concisely but epitomise their chapters with an extended bibliography. Obviously, during the past 60 years, the metoric advances are voluminous and to cover every account of genes, chromosomes, and sex in a single volume format would be a herculean task. Therefore, a few specific topics are chosen, which may be of great interest to scientists and clinicians. The seasoned scientists who love to inquire about the role of genes in sex determination should find the original work of these notable contributors very enlightening. This volume is intended for advanced students who want to keep abreast as well as for those who indulge in the search for genes of sex determination.